2010
DOI: 10.1007/s11998-010-9299-5
|View full text |Cite
|
Sign up to set email alerts
|

Service life prediction of organic coatings: electrochemical impedance spectroscopy vs actual service life

Abstract: Electrochemical impedance spectroscopy (EIS) is used to derive an expression for predicting the service life of organic coating in a C4-type environment (industrial and costal areas with moderate salinity) as defined in ISO 12944 standard for paints and varnishes-corrosion protection of steel structures by protective paint systems. Three coating systems with a record of 2, 5, and 10 years of durability were selected for the study. The selection was also based on proven composition and dry film thickness (DFT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 13 publications
0
17
0
3
Order By: Relevance
“…The electrical capacitance has information on the conductive properties of materials and their chemical composition. Recently, several authors have replaced this pure capacitance by a CPE, because this has been considered an improvement in the settings of the theoretical equations regarding experimental results [37][38][39], for example, in predicting the useful life of coatings and surface roughness heterogeneity resulting from the presence of impurities, fractality, dislocations, adsorption of inhibitors, or formation of porous layers [40][41][42][43][44][45][46][47] Caputo-Fabrizio approach, the Bode plots exhibit changes in the cutoff frequency, hence the phase shift and the decrease of the magnitude. For the range of frequency 10 to 10000 rad/s a shift in the magnitude and phase is shown, which implies that the proposed circuit better defines these frequencies.…”
Section: Polarizable Electrodementioning
confidence: 99%
“…The electrical capacitance has information on the conductive properties of materials and their chemical composition. Recently, several authors have replaced this pure capacitance by a CPE, because this has been considered an improvement in the settings of the theoretical equations regarding experimental results [37][38][39], for example, in predicting the useful life of coatings and surface roughness heterogeneity resulting from the presence of impurities, fractality, dislocations, adsorption of inhibitors, or formation of porous layers [40][41][42][43][44][45][46][47] Caputo-Fabrizio approach, the Bode plots exhibit changes in the cutoff frequency, hence the phase shift and the decrease of the magnitude. For the range of frequency 10 to 10000 rad/s a shift in the magnitude and phase is shown, which implies that the proposed circuit better defines these frequencies.…”
Section: Polarizable Electrodementioning
confidence: 99%
“…This is in concordance with the well-known, superior performance of epoxy coatings over the polyurethane coatings under immersion conditions. 14 The oscillatory behaviour of impedance during the EIS tests has been observed previously and might be explained by pore blockage by corrosion products and the random formation of macroscopic perforations in the coating. 37 Although the authors refer to the observed oscillations as a drawback of the EIS method and its failure to give reproducible results, it should be noted that the result in fact shows the ability of EIS to authentically reflect the true state of the coating.…”
Section: Eis Resultsmentioning
confidence: 54%
“…14 Impedance greater or equal to 10 9 Ω corresponds to excellent protecting properties of coatings which provide almost purely capacitive behaviour over long exposure periods. 15 The described EIS model may be applied to various industrial coating types and thicknesses providing a universal tool for coating quality and protective ability comparison [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Based from the plots in Figure 11, two time constants are operating and the spectra could be analysed in terms of an equivalent circuit for a defective coating. e equivalent circuit for a defective coating is made up of the resistance of the test electrolyte, the capacitance of the intact coating layer, the pore resistance due to penetration of electrolyte, the polarization resistance of the substrate, and the double layer capacitance at the substrate/electrolyte interphase (Gonzalez-Guzman et al, 2010;Shreepathi et al, 2011).…”
Section: Results From Electrochemical Evaluationmentioning
confidence: 99%